Antimicrobial activity of Pavetta indica leaves - Vinod Kumar Gupta, Charanjeet Kaur, Aritra Simlai and Amit Roy (Journal of Applied Pharmaceutical Science, 2013)
Antimicrobial activity of the aqueous and organic solvent extracts of the leaves of Pavetta indica were tested against Bacillus subtilis, Escherichia coli and Saccharomyces cerevisiae using disc diffusion assay. Most of the leaf extracts showed bactericidal activity against B. subtilis. None of the extracts exhibited any activity against E. coli and S. cerevisiae. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), thermal stability and qualitative phytochemicals studies were performed. Both MIC and MBC of the aqueous and methanol extracts were found to be between 1.95 - 7.81 mg/ml. The activity of aqueous and methanol extracts were found to be stable despite thermal treatment. Phytochemical analysis of aqueous extract revealed the presence of flavonoids, saponins and carbohydrates. Methanol extract was found to be positive for saponin and cardiac glycosides. TLC and bioautography were also done to identify the active fractions responsible for the antimicrobial activities. Results showed the presence of a number of bactericidal components. The study suggests P. indica to be a source for isolation of antibacterial compounds for human health care and use as preservatives in food processing industry.
Keywords: Pavetta indica, Antibacterial act